2012
DOI: 10.1007/s12070-011-0451-z
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Videostroboscopic Assessment of Vocal Pathologies

Abstract: Successful treatment of bilateral vocal fold lesions depends on the accuracy of the diagnosis. The application of stroboscopy to the study of vocal fold vibration has led to dramatic advances in the understanding of vocal fold physiology. Laryngeal stroboscopy is the state of the art diagnostic tool and this technique provides valuable information about the nature of the vibration and a visual image that can be used both for immediate analysis and as a permanent record for comparison of repeated examination at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
3
6
0
2
Order By: Relevance
“…This figure is consistent with Banjara et al [12] , Guha et al [14] and Raja et al [15] . This is due to the voice overactivity in that age group in this society.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This figure is consistent with Banjara et al [12] , Guha et al [14] and Raja et al [15] . This is due to the voice overactivity in that age group in this society.…”
Section: Discussionsupporting
confidence: 93%
“…This figure is against with Banjara et al [12] , where males predominate (61.6%) compared with females (38.4%) in a ratio of 1.5:1 in cases of benign vocal cord lesions , it is also against with Toran K. C. et al [13] and against Guha et al [14] . This may be due to the small size of this study .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our study hoarseness was found in (58.33% )was the most common symptom . Similar to the study carried by Hansa Banjara (2012) who (4) also found hoarseness as most common symptom (20.54%) .…”
Section: Figure 2: Mpt Analysissupporting
confidence: 89%
“…A literatura evidencia a grande ocorrência de lesões benignas das pregas vocais em docentes (Braga et al, 2006;Woźnicka, Niebudek-Bogusz, Morawiska, & Śliwińska-Kowalska, 2017;Mobarsa, Samdani, & Gurjar, 2018;Vivek, Sabah, Nidhi, & Neethu, 2018) do sexo feminino (Braga et al, 2006;Banjara, Mungutwar, Singh, Gupta, & Singh, 2012;Mobarsa et al, 2018). O nódulo vocal é a lesão mais frequente (Banjara et al, 2012;Woźnicka et al, 2017;Mobarsa et al, 218;Vivek, et al, 2018) e o tipo mais comum de Research, Society and Development, v. 9, n. 7, e584974397, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4397 13 fechamento glótico encontrado na presença de nódulos foi o padrão de fenda em ampulheta (Banjara et al, 2012;Vivek, et al, 2018). Isto converge com nossos achados em que, das 32 professoras, 12 apresentavam nódulos vocais.…”
Section: Variáveis Correlacionadasunclassified